Research priorities for seabirds: improving conservation and management in the 21st century - Lewison, R. (2012)
Seabirds, a diverse group of bird species associated with the ocean during a significant part of their lives, are facing a growing number of threats in both their terrestrial and marine habitats, and many populations have experienced dramatic changes over the past decades. Seabirds are among the best-studied of marine vertebrates; years of research have played a central role in improving our understanding of seabird populations and have informed a broader understanding of marine ecological processes. In an effort to encourage future research and guide science directed at improving seabird population and habitat management and conservation, we identify 20 key areas where continued, robust and comprehensive inter-disciplinary science is most needed. Twenty-seven seabird researchers from 9 nations identified the 20 highest priority research questions, which were organized into six general categories: (i) population dynamics, (ii) spatial ecology, (iii) tropho-dynamics, (iv) fisheries interactions, (v) response to global change, and (vi) management of anthropogenic impacts (focusing on invasive species, contaminants and protected areas). While this is not an exhaustive list of all research needed to address the myriad conservation challenges seabirds face, the results of this effort represent an important synthesis of current expert opinion across sub-disciplines within seabird ecology. As this synthesis highlights, research, in conjunction with direct management, education, and community engagement, can play an important role in facilitating the conservation and management of seabird populations and of the ocean ecosystems on which they and we depend.